Everything, everywhere, all at once - Surveillance and molecular epidemiology reveal Melissococcus plutonius is endemic among Michigan, US beekeeping operations - Peter D. Fowler; Upasana Dhakal; Jeff H. Chang; Meghan O. Milbrath (PLoS ONE, 2025)
European foulbrood (EFB) is a severe bacterial disease of honey bee brood often leading to significant declines in colony health and honey production. The dearth of data on this disease in the United States (US) complicates response efforts. In 2021 and 2022 we conducted a two-year cross-sectional surveillance study among Michigan beekeepers to establish baseline pathogen and disease prevalence. We combined this surveillance with molecular epidemiology to investigate genetic diversity, and transmission dynamics of Melissococcus plutonius, the causative agent of EFB, in US honey bee colonies. PCR screening detected M. plutonius in all 15 migratory and stationary beekeeping operations and in 6 of 14 hobby beekeeping operations. Infection and disease were found to be seasonal, with prevalence of both peaking in June when over half the colonies were infected, and over 20% had clinical EFB. Whole genome, single nucleotide polymorphism analysis revealed wide genetic diversity even within a single hive. Operations often had multiple genotypes present which varied from year to year, consistent with high rates of transmission and reinfection. Prevalence and whole genome data provided here will be critical in tracking the efficacy of mitigation efforts and underscore the necessity of additional epidemiological investigations.